Molecular Screening Tools to Study Arabidopsis Transcription Factors - Wehner, Nora; Weiste, Christoph; Dröge-Laser, Wolfgang (Frontiers in Plant Science, 2011)
In the model plant Arabidopsis thaliana, more than 2000 genes are estimated to encode transcription factors (TFs), which clearly emphasizes the importance of transcriptional control. Although genomic approaches have generated large TF Open Reading Frame (ORF) collections, only a limited number of these genes is functionally characterized, yet. This review evaluates strategies and methods to identify TF functions. In particular, we focus on two recently developed TF screening platforms, which make use of publi-cally available GATEWAY® compatible ORF collections. (1) The Arabidopsis thaliana TF ORF over-Expression (AtTORF-Ex) library provides pooled collections of transgenic lines over-expressing HA-tagged TF genes, which are suited for screening approaches to define TF functions in stress defense and development. (2) A high-throughput microtiter plate based Protoplast Trans Activation (PTA) system has been established to screen for TFs which are regulating a given promoter:Luciferase construct in planta.